Cytotoxic Activity of Methoxy-4’amino Chalcone Derivatives Against Leukemia Cell Lines - Arina Novilla; Mustofa Mustofa; Indwiani Astuti; Jumina Jumina; Hery Suwito (Molecular and Cellular Biomedical Sciences, 2019)
Background: Chemotherapy is a common treatment for leukemia as well as in other cancer treatment. The lack of tumor selectivity and development of multi-drug resistance by chemotherapy caused the development of new strategy in cancer treatment become a pressing need. This study was performed to evaluate the anticancer activity and selectivity of seven derivatives of chalcones against K562 and HL-60 leukemia cell lines. Materials and Methods: The cytotoxicity of chalcone’s seven derivatives (compound 1-7) was tested by using MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxyme-thoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) method. The percentage of cell mortality data was calculated then the IC50 was analyzed using probit analysis (SPSS 17). The selectivity index (SI) then calculated from IC50 ratio of normal lymphocyte cells and cancerous cells line (HL-60 and K562).Results: The IC50 of almost all seven tested compounds were lower in HL-60 cell lines than K562 cell lines, except for Compound 7. The number and position of methoxy groups in chalcone derivatives influenced the anticancer and cancer selectivity of chalcone derivatives.Conclusion: The results revealed that the number and position of methoxy groups in chalcone derivatives influenced the anticancer and cancer selectivity of chalcone derivatives.Keywords: anticancer, chalcone derivatives, methoxy-4’-amino chalcone, leukemia, cytotoxic, selectivity